Improving Employee Performance and Work Motivation Through Compensation and Leadership Style - Putri, Nopela; Sarmigi, Elex; Desiana, Desiana (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This research aims to determine whether compensation and leadership style can influence employee performance, mediated by work motivation. This research uses a quantitative approach with primary data collected with the help of an online questionnaire using Google Forms. The population of this research is all banking employees in Sungai Penuh City, with a sample of 95 employees. This research data was analyzed using the Structural Equation Model (SEM) using the SMART PLS 3.2.9 application. The results of this research found that work motivation has a direct effect on employee performance, and compensation also has a direct impact on work motivation. Meanwhile, compensation and leadership style do not directly affect employee performance, and work motivation with compensation does not directly affect leadership style. Furthermore, the results of hypothesis testing prove that work motivation can mediate compensation and employee performance, while work motivation cannot mediate between compensation and leadership style. Also, Leadership style variables cannot mediate work motivation, employee performance, compensation, and performance.